Analysis of The Influence of Customer Satisfaction, Experiental Marketing and Product Quality on Loyalty of Uniqlo Customers - Anton Yuliansyah; Silvia Ekasari; Endang Meliani; Hery Purnomo; Musran Munizu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study intends to examine how product quality and experiential marketing affect customer loyalty and consumer happiness. A quantitative analysis method was employed in the analysis. the Likert scales. The path analysis approach is the one the author used to process the data. Purposive sampling was used in this investigation, and the sample size was 100 respondents. The information gathered is primary information, the outcome of respondents' responses to the questionnaires that were delivered. The findings indicated that the experiential marketing variable had a significant impact on customer satisfaction, that product quality variables significantly influenced customer satisfaction variables, that experiential marketing variables and product quality also had a significant impact on customer satisfaction variables, and that customer loyalty variables were significantly influenced by both of these variables.